Swallowing behaviours and feeding environment in relation to communication development from early infancy to 6 years of age: a scoping review protocol - Heather Flowers; Daniel Bérubé; Mona Ebrahimipour; Marie-France Perrier; Sarah Moloci; Stacey Skoretz (BMJ Open)
Introduction Understanding the influences of early swallowing function and feeding environment on the development of communication will enhance prevention and intervention initiatives for young children. This scoping review will help elucidate key elements affecting the developmental trajectory of communicative systems, typically robust and well-developed by formal school entry. We aim to (1) map the current state of the literature in a growing field of interest that has the potential to advance knowledge translation, (2) identify existing gaps and (3) provide research direction for future investigations surrounding feeding-swallowing functions and environment that support or forestall communication development in young children.Methods and analysis We are proposing a scoping review to identify the breadth and depth of the existing literature regarding swallowing-feeding functions and environment relative to the onset and progression of communicative behaviours from infancy to 6 (<6;0) years of age. Our protocol delineates rigorous methods according to Arskey and O’Malley’s framework and includes elaborations by Levac and colleagues. We will search the literature based on 10 databases, 17 peer-reviewed journals, 4 conference proceedings and 6 grey literature sources. Two authors will independently screen abstracts and review full articles, remaining blind to each other’s results. A third author will contribute to resolving any discrepant results from both the abstract and article review. Subsequently, we will extract data and chart information from accepted articles using a pre-established data collection form. We will stratify results according to healthy versus impaired swallowing-feeding functions and communication development.Ethics and dissemination Our scoping review does not require ethical approval. We will disseminate our final study results through international and national conference presentations, publication in a peer-reviewed journal and knowledge translation activities with stakeholders.